計畫行為理論高中生觀點分析學習歷程檔案實施與效益之研究 A Study on the Implementation and Benefits of Academic Portfolio Based on the High School Students' Perspective of the Theory of Planned Behavior - 簡瑋成 Wei-Cheng Chien (National Taiwan Normal University, 2024)
本研究以計畫行為理論為基礎，聚焦高中生對學習歷程檔案的信念、態度、主觀規範、知覺行為控制、意向與投入的狀況和關係模型，並探討投入行為對核心素養、生涯規劃與升學選擇的影響。本研究以紙本問卷調查臺灣高中生，最終回收有效問卷3,638份。研究結論包括高中生對學習歷程檔案良好結果助益信念有所不足，態度略偏負面，不過，擁有準備學習歷程檔案的資源與機會還算充足，且尚能自主掌控學習歷程檔案的準備。而教育利害關係人對學習歷程檔案略表不認同，但是，認為高中生應努力充實學習歷程檔案。再者，高中生擁有學習歷程檔案準備的意願與實際投入行為，並以知覺行為控制為影響高中生準備意願與投入行為的最重要因素。最後，研究發現高中生參與學習歷程檔案的準備有益於孕育核心素養與發展生涯規劃，且略有利於提高升學意向，對部分入學管道選擇也發揮了微小影響。對未來研究建議方面，建議以高中生學習歷程資料庫中學生實際上傳的資料進行客觀分析，並建立長期追蹤調查資料，以分析趨勢變化。同時，也建議學校端與政府政策應加強宣導學習歷 程檔案與制度調整，學校應藉由學習歷程檔案實踐素養導向教育與生涯發展教育的理念，教師也應著重加強學生對學習歷程檔案的自信心與自主權。 Research Motivation and Purpose The Academic Portfolio, a pivotal component of the Master Framework for the Curriculum Guidelines of 12-Year Basic Education, is designed to promote literacy education and support high school students in career planning. Determining the effectiveness of the Academic Portfolio and understanding students' perspectives and participation is necessary. A nationwide survey, in conjunction with empirical data, is required to validate the effectiveness of the Academic Portfolio and its influence on higher education choices. This study used the framework of the Theory of Planned Behavior (TPB) to examine high school students' beliefs, attitudes, subjective norms, perceived behavioral control, intention, and behavior toward the Academic Portfolio and the influence of behavior on core competencies, career planning, and higher education choices. Literature The Academic Portfolio refers to a method of assessment that documents students' learning processes, growth, and changes by collecting various processes and outputs, thereby authentically reflecting students' learning performance. The Portfolio is accessible not only to students but also to peers, parents, and teachers, who can observe the students' learning outcomes and related achievements. Additionally, observers can understand students' strengths and weaknesses, intrinsic motivations, learning feedback, and self-actualization throughout the learning process. The 12-Year Basic Education program requires that students complete an Academic Portfolio in high school. The K-12 Education Administration of the Ministry of Education has established a student Academic Portfolio database for the senior secondary education stage that hosts relevant data uploaded by Taiwanese school students within a specified time frame. Subsequently, when students apply to universities, their files in the database, with their consent, can be provided to the applying schools as a reference for admissions. The greatest benefit of this system is that it allows universities to understand the students' interests and aspirations without requiring high school seniors to create additional résumé files. The database contains information on students' basic information, course records, course learning outcomes, diverse performances, student statements, and other materials (Lin, 2021; Ministry of Education, 2019; Shih et al., 2023). Following the implementation of the 108 Curriculum Guidelines, promoting the Academic Portfolio system has become a key policy initiative. Core competencies and practical learning activities within schools are imperative. However, the promotion of the Academic Portfolio system has encountered numerous misunderstandings and difficulties, not only from students and parents but also from school teachers and the general public (Lin, 2021; Liu, 2019). Therefore, this study examined the current implementation status of this initiative from the perspective of students by using a large-scale survey. The TPB posits that the likelihood of an individual engaging in a particular action is primarily determined by the individual's intention to perform that action, which is influenced by three main factors: attitude, subjective norms, and perceived behavioral control (Ajzen, 1991; Fishbein & Ajzen, 1977). Within the TPB model, an individual's engagement in a behavior is determined by their specific behavioral intention, which is influenced by their attitude, subjective norms, and perceived behavioral control (Chang et al., 2021;Wang et al., 2020). These factors can be traced back to behavioral beliefs, normative beliefs, and control beliefs, respectively. Behavioral beliefs refer to an individual's favorable thoughts about the outcomes of completing a specific behavior. Normative beliefs involve the perceived behavioral expectations of significant others, such as relatives, friends, and teachers. Control beliefs refer to an individual's perception of the resources and opportunities available to them or the barriers they may encounter when undertaking a specific behavior (Ajzen, 1991; Davis et al., 2002). Intention, in this context, represents the strength of an individual's willingness to perform a specific behavior. Attitude refers to an individual's positive or negative feelings toward the behavior. Subjective norms refers to the perceived social pressure to perform or not perform the behavior. Perceived behavioral control refers to an individual's perception of the The definitions of all these TPB-related variables in the context of this study are as follows: 1.Behavioral beliefs: High school students' beliefs that engaging in the preparation of the Academic Portfolio will lead to favorable outcomes, categorized into affective and instrumental beliefs. 2.Normative beliefs: Evaluations of the Academic Portfolio by high school students' teachers, peers, relatives, and societal norms. 3.Control beliefs: High school students' perceptions of the time, resources, and opportunities they have for preparing the Academic Portfolio. 4.Attitude: High school students' positive or negative evaluations of the Academic Portfolio. 5.Subjective norms: The social pressure high school students perceive in relation to the Academic Portfolio, meaning the influence of significant others (teachers, peers, relatives, societal norms) on students' attitudes and behaviors regarding the Portfolio. 6.Perceived behavioral control: High school students' perception of their autonomy and confidence in preparing the Academic Portfolio. 7.Behavioral intention: The subjective probability that high school students will engage in preparing the Academic Portfolio, reflecting their willingness to do so. 8.Behavior: The degree to which high school students are actually involved in the preparation of the Academic Portfolio. Methods This study primarily analyzed feedback from high school students about the Academic Portfolio system. Data were collected through a paper-based questionnaire survey from second- and third-year high school students in Taiwan. A total of 120 high schools of various types were randomly selected, and 40 students were randomly chosen from each school, resulting in a total of 4,800 questionnaires being distributed, from which 3,638 valid responses were collected. Results and conclusion: 1.High school students still lack sufficient belief in the benefits of the Academic Portfolio. 2.Educational stakeholders express slight disagreement with the Academic Portfolio. 3.High school students generally have adequate resources and opportunities to prepare their Academic Portfolio. 4.High school students hold a somewhat negative attitude towards the Academic Portfolio. 5.Educational stakeholders believe that high school students should make efforts to enrich their Academic Portfolios.